Distinguishing a Trichilemmal Cyst From a Pilomatricoma With Ultrasound. (25th April 2020) - He, Ping; Chen, Wen; Zhang, Qian; Cui, Li‐Gang; Zhang, Qian
Abstract : Objectives: To determine whether ultrasound (US) could distinguish a trichilemmal cyst from a pilomatricoma preoperatively. Methods: Ultrasound images of 61 pathologically proven trichilemmal cysts and 90 pathologically proven pilomatricomas were analyzed retrospectively. Two radiologists evaluated several US features. The sensitivity, specificity, Youden index, and predictive values of statistically significant US features were assessed. Parallel combined tests, serial combined tests, or both were performed to identify US features with high statistical significance. Results: Results from individual US features were not satisfactory; however, serial combined tests that included absence of complete internal echogenic foci, absence of a hypoechoic rim, absence of peritumoral hyperechogenicity, and absence of vascularity showed higher diagnostic utility. The sensitivity, specificity, Youden index, positive predictive value, and negative predictive value for correctly identifying a trichilemmal cyst were 74%, 88%, 0.62, 80%, and 83%, respectively. If 1 of these 4 US features was not a match for a trichilemmal cyst, pilomatricoma was considered. Conclusions: It may be possible to distinguish trichilemmal cysts from pilomatricomas preoperatively using US. A combined test is superior to using any individual US feature.